From Kendal's Coffee House to Great George Street - Roberts, Gwilym (Thomas Telford, 1995)
This history of the various headquarters of the Institution of Civil Engineers traces the journey from the first meetings of a group of young engineers in Kendal's Coffee House, Fleet Street to the grandeur of the present headquarters at Great George Street. The book is highly illustrated and contains many photographs.